Allergenic activity of Pseudoterranova decipiens (Nematoda: Anisakidae) in BALB/c mice - Ludovisi, Alessandra (Parasit Vectors, 2017)
BACKGROUND: Anisakis simplex is the only fishery-product associated parasite causing clinical allergic responses in humans so far. However, other anisakids, due to the presence of shared or own allergens, could also lead to allergic reactions after sensitization. The aim of this study was to determine if Pseudoterranova decipiens belonging to the family Anisakidae has allergenic activity and is able to induce sensitization after oral administration in a murine (BALB/c mice) model. RESULTS: The ingestion of A. pegreffii proteins by BALB/c mice, which had been previously sensitized by intraperitoneal inoculation with the corresponding live L3 larvae, triggers signs of allergy within 60 min, whereas P. decipiens did to a lesser extent. Beside symptoms, allergic reactions were furtherly supported by the presence of histamine in sera of sensitized mice. Specific IgG1 and IgE responses were detected in sera of all sensitized mice from week four. Specific IgG2a response was detected in sera from mice sensitized to P. decipiens. After polyclonal or specific activation with anti-CD3/anti-CD28 or antigens, respectively, splenocytes from mice infected i.p. with A. pegreffii or P. decipiens larvae showed significantly higher production of IL-10 than naïve mice. After stimulation with specific antigens, significantly higher IL-5 and IL-13 amounts were produced by specific antigen stimulated splenocytes than by the naïve cells; only P. decipiens proteins induced IFN-ɣ. CONCLUSIONS: The overall results suggest that infection with P. decipiens can sensitize mice to react to subsequent oral challenge with anisakid proteins, as described for A. simplex (sensu stricto) and A. pegreffii infections. The results show that anisakid proteins induce a dominant Th2 response, although P. decipiens could also induce a mixed type 1/type 2 pattern.